The Nature of Corporate Governance and Performance in the Conditions of Ownership Concentration - Leković, Božidar S; Marić, Slobodan M (Industrija, 2016)
The central research question and purpose of this topic is oriented on the analysis of concentration scope of share capital ownership in Serbia, and their relation to corporate performance.The article also attempts to give a suitable reply to the question as to what extent the concentration of share capital ownership has changed in comparison to previous, which was formed at the beginning of the process of transition and privatisation of the public property, which was used as the foundation for forming the corporate sector. The answers to these questions will be used to point to the nature of the corporate sector in Serbia, and the degree of development of the securities market. Research methodology involves the use parametric procedures due to the characteristics of the selected variables and the number of observations in the sample. Univariate ANOVA procedures and Pearson’s correlation coefficient will be used.The corporate sector in Serbia achieves positive results but does not receive adequate market verification due to extreme ownership concentration and the dominant influence of the majority, or several large shareholders. Due to the privileged position of a small number of privileged shareholders, such a situation results in the expropriation of small shareholders, who remain helpless due to underdeveloped mechanisms of legal and institutional protection.